A spreadsheet program for making a balanced Latin Square design - Kim, Beob G.; Stein, Hans H. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Latin square designs are often employed in animal experiments to minimize the number of animals required to detect statistical differences. Generally, potential carryover effects are not balanced out by randomization. Systemic methods are available for equalizing the residual effects. We have developed an Excel® spreadsheet-based program, the Balanced Latin Square Designer (BLSD), to facilitate the generation of Latin squares balanced for carryover effects. The program allows a user to input the number of treatments that is equal to the number of animals and periods in a square. A user may also input the number of squares. Then, the BLSD automatically generates Latin squares balanced for the first order carryover effects. For an even number of treatments, each treatment immediately precedes and follows every other treatment exactly once in the square. For Latin squares with an odd number of treatments, the first order residual effects can be balanced only if they are replicated an even number of times. The program also displays a table for an experimental schedule sorted by period and animal. The BLSD allows animal scientists to quickly and accurately generate Latin squares balanced for the first order carryover effects. The program is freely available upon request.